The Influence of the Problem-Based Learning (PBL) Model Assisted by Wordwall Media on Elementary School Students' Conceptual Understanding - Fadila Ramdhani; Sabahiyah Sabahiyah (Journal of Educational Studies, 2025)
During the learning process, students appeared less enthusiastic in paying attention to the teacher’s explanations, they seemed uninterested and bored because the learning activities were predominantly teacher-centered and provided limited opportunities for students to think and actively engage in learning. Furthermore, students were rarely given the chance to interact with their peers to share ideas or thoughts in solving a problem, resulting in a poor understanding of the concepts being studied. This study aims to determine whether the Problem Based Learning model assisted by Wordwall media influences students’ conceptual understanding in the Science and Social Studies (IPAS) subject of fifth-grade students at SD Negeri 3 Mamben Lauk. The population of this study consisted of 43 students, and the entire population served as the sample. This research employed a quasi-experimental design with The Posttest Only Control Group Design. Data on students' conceptual understanding were collected through multiple-choice tests. The data were analyzed using the Independent Sample T-Test technique. The analysis results showed that the experimental class had an average score of 77.95, while the control class had an average score of 70.43. The T-test results yielded a significance value of 0.003 < 0.05. Thus, it can be concluded that there is an influence of the Problem Based Learning model assisted by Wordwall media on students' conceptual understanding in the IPAS subject of fifth-grade students at SD Negeri 3 Mamben Lauk.